2017
DOI: 10.1103/physrevb.96.045107
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of how the heavy-fermion state develops in CeCoIn5

Abstract: Heavy fermion materials gain high electronic masses and expand Fermi surfaces when the high-temperature localized f electrons become itinerant and hybridize with the conduction band at low temperatures. However, despite the common application of this model, direct microscopic verification remains lacking. Here we report high-resolution angle-resolved photoemission spec-1 arXiv:1610.06724v1 [cond-mat.str-el]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 52 publications
20
77
0
1
Order By: Relevance
“…We found a nearly flat band at the Γ point at low temperatures. Bands away from the Γ point have no flat character, indicating the Ce 4f-electron contribution appears mainly around the Γ point, which is similar with other cerium based heavy-fermion compounds [17][18][19]. We found that Ce2IrIn8 has a similar band structure with the CeMIn5 (M = Co, Rh, Ir) compounds near the Fermi level: hole pockets around the Γ point and electron pockets…”
supporting
confidence: 76%
See 2 more Smart Citations
“…We found a nearly flat band at the Γ point at low temperatures. Bands away from the Γ point have no flat character, indicating the Ce 4f-electron contribution appears mainly around the Γ point, which is similar with other cerium based heavy-fermion compounds [17][18][19]. We found that Ce2IrIn8 has a similar band structure with the CeMIn5 (M = Co, Rh, Ir) compounds near the Fermi level: hole pockets around the Γ point and electron pockets…”
supporting
confidence: 76%
“…If we add the contributions from the α, β electron pockets, we may get similar value 0.2±0.05 in CeCoIn5. [17] CONCLUSIONS To summarize, we performed high-resolution on-resonant temperature dependent study on the heavy-fermion compound Ce2IrIn8 across the coherent temperature. We found a nearly flat band near the Fermi level around the Γ point showing no big difference in kF, which seems to challenge the small-to-large Fermi surface scenario in the heavy-fermion compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reconciles, within a single experiment, the existence of a large Fermi volume at T T * K with vanishing Kondo weight at the QPT. Since this CEF-induced mechanism appears to be generic, we expect similar behavior of other Ce-and Yb-based heavy-fermion compounds [8,10,35,36] This supplement describes specifications of the experimental setup as well as the definition of the multi-orbital Anderson lattice model and details of the dynamical mean-field theory (DMFT) calculations with the non-crossing approximation (NCA) as the impurity solver.…”
mentioning
confidence: 94%
“…To further quantitatively investigate the hybridization of conduction bands and f electrons, we zoom in the spectral feature around Γ in the vicinity of E F and then performed the PAM fitting, which has been proved an effective way to study the f electron behaviors [10,13]. Details of the band dispersion extraction and the PAM fitting can be found in the supplementary material [28].…”
mentioning
confidence: 99%